Role of Surgery in the Outcome Difference of Gastroschisis between High-income and Lowmiddle- income Countries: A Review (Dhaka Shishu (Children) Hospital Journal, 2023)
Gastroschisis is a major congenital abdominal wall defect where the abdominal viscera comes out through a gap right to the umbilicus. The management of gastroschisis requires prompt and aggressive medical and surgical intervention immediately after birth. However, there is a notable disparity in mortality rates between developed countries and LMICs. Despite various surgical technique adjustments, LMICs still suffer from a high mortality rate, with certain centers reporting a 100% mortality rate. This article seeks to examine the literature and evaluate the impact of surgical techniques on the outcome of gastroschisis.DS (Child) H J 2022; 38(2): 103-106